Enhancing the Theory of Planned Behaviour by Incorporating Social Marketing Behavioural Enhancers: A First VS Second Order Confirmatory Factor Analysis Approach - Christian, Ayikwa Lutete; W., De Jager Johan; Dion, Van Zyl (Journal of Economics and Behavioral Studies, 2019)
This study investigated the need to extend the TPB model to SMBE variables as suggested by Ayikwa and De Jager (2017) in the quest to better understand sexual behavioural patterns using the Confirmatory Factor Analysis (CFA) approach. The main research question to be answered: "how the TPB and SMBE variables should be structured into a validated CFA model?" Data were carefully collected in South Africa’s Gauteng Province using a disproportionate multi-stage stratified random sampling method to retain 607 respondents. The survey questionnaires distributed consisted of revisited pre-existing instruments. The data were then analysed by CFA model that followed Exploratory Factor Analysis (EFA) to determine the suitability of the sample size. Assessment of the second order extended TPB model confirmed that it is worthwhile to integrate SMBE variables while extending the TPB model in the context of HIV/AIDS related behaviours.